Cognitive Support Technologies for Adolescents with Disabilities: Impact on Educator Perceptions of Capacity and Opportunity for Self-Determination - Shogren, Karrie A.; Wehmeyer, Michael L.; Davies, Daniel; Stock, Steven; Palmer, Susan B. (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2015)
Research has suggested that adding cognitive support technologies to the transition planning process enhances student self-determination above and beyond traditional, book or paper-based self-determination curricular materials. However, limited research has examined how teachers perceive the impact of cognitive support technologies on student capacity and opportunity for self-determination. The present study used multivariate analysis of covariance to examine teacher perceptions of student capacity and opportunity for self-determination over time based on group random assignment to a self-determination curricula alone group or a self-determination curricula plus cognitive support technology group. The impact of disability label (learning disability vs. intellectual disability) on educator perceptions was also examined. Findings suggest a complex pattern of differences over time; there was a multivariate effect for the interaction of time, disability, and technology access, but when decomposing these differences at the univariate level, the primary differences were in educator ratings of capacity, not opportunity. Differences based on disability label were also found, with educators rating students with intellectual disability significantly lower in their capacity for self-determination, but not opportunity. Implications for future research and practice are discussed.